Factors Influencing Consumer Trust and Loyalty in E-Commerce: A Case Study of Website PT. Wearinasia Internet Akselerasi: - Song, Renih (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
As technology advances, so does the expansion of e-commerce, as seen by platforms such as wia.id, operated by Wearinasia Internet Akselerasi. This study looks at the elements influencing e-commerce trust and loyalty at wia.id, an Indonesian e-commerce website specializing in active lifestyles, content production, and travel items. The study investigates how user interface quality (UIQ), information quality (IQ), perceived security risk (PS), perceived privacy (PP), and e-commerce awareness (EA) influence e-commerce trust (ET), and then how ET affects e-commerce loyalty (ECL). The data was analysed using PLS-SEM. The main findings show that information quality and perceived security risk significantly and positively influence e-commerce trust, demonstrating that consumers appreciate accurate information and secure transactions on the platform. Interestingly, user interface quality, perceived privacy, and e-commerce awareness did not significantly influence trust, indicating that consumers may not value these variables or need to be more efficiently applied. Finally, the study finds that e-commerce trust is critical for promoting customer loyalty, since users who trust wia.id are more likely to stick with the platform.